Effect of sulfur doping on structural reversibility and cycling stability of a Li2MnSiO4 cathode material. Issue 35 (17th August 2018) - Wu, Xia; Zhao, Shi-Xi; Yu, Lü-Qiang; Yang, Jin-Lin; Nan, Ce-Wen
Abstract : Sulfur has been successfully employed into Li2 MnSiO4 and results in a high initial discharge capacity and excellent cycling stability. Abstract : Based on the existing calculation reports, sulfur doping is an effective approach to alleviate the structure collapse of Li2 MnSiO4 during cycling. Herein, we investigate the feasibility and limitations of S doping in Li2 MnSiO4 by experiment. In our work, the solid solubility of S is confirmed and exceeding the threshold results in MnS impurity. The existence state and site of the S element in a Li2 MnSiO4 crystal structure is also confirmed. It is found that S doping significantly improves the structural reversibility and cycling stability. Compared with a pristine sample, a 1mol% S doped sample exhibits a much higher initial coulombic efficiency (88.3%), excellent capacity retention (98% at 10 th cycles for instance) and enhanced rate performance. Moreover, the 1mol% S doped sample can retain a discharge capacity of 137 mA h g −1 after 30 cycles while the pristine sample only has 61.6 mA h g −1 . This study confirms the effectivity of S doping in suppressing the structural distortion in Li2 MnSiO4 .